Efficacy of cyclosporin A in the treatment of acute posterior multifocal placoid pigment epitheliopathy - Nowak, Michał S.; Jurowski, Piotr; Kaszuba-Bartkowiak, Katarzyna (Archives of Medical Science, 2009)
Aim of the study is report a case of a female patient with acute posterior multifocal placoid pigment epitheliopathy (APMPPE) in whom remission was obtained after systemic cyclosporin A treatment had been applied. The presented case confirms the efficacy of oral cyclosporin A (Sandimmun Neoral) treatment in selected types of choroiditis including patients with APMPPE resistant to steroid therapy.